Enabling environments for nutrition advocacy: A comparison of infant and young child feeding and food fortification in Nigeria - Resnick, Danielle; Anigo, Kola; Anjorin, Olufolakemi Mercy (International Food Policy Research Institute, 2021)
The importance of an enabling environment for effective nutrition advocacy is well-recognized, and several key elements of such an environment have been well-established in existing research. However, nutrition policies are multi-faceted, and advocates may target different elements of the process, from agenda setting to design to implementation. As a result, enabling environments are neither uniform nor static. Drawing on 66 interviews with a diverse group of stakeholders in Nigeria at the federal and subnational level, we examine some of the factors that have facilitated or hindered the ability of advocates to influence implementation in the domains of infant and young child feeding (IYCF) and large-scale food fortification. In doing so, we show the importance of considering the politics, institutions, and resources specific to discrete categories as well as the characteristics of the broader system in which advocates are operating. By working across these two levels, advocates can both be reactive to the prevailing enabling environment as well as proactively consider strategies for overcoming obstacles.